ChemInform Abstract: NIS‐Mediated Ring‐Closure/Opening Cascade Reactions of Allylamides: An Expedient Route to Oxazolines. Issue 1 (17th December 2015) - Hu, Yancheng; Li, Xincheng; Wan, Boshun
Abstract: N‐allyl‐N‐methylbenzamide as well as N‐benzyl‐ and N‐phenyl‐N‐propargylbenzamides do not give the desired product.